Cookies Tepung Umbi Gembili dengan Variasi Perbandingan Tepung Mocaf dan Persentase Tepung Cangkang Telur - Ahmad Malik Khasanuddin; Maria Ulfah; Adi Ruswanto (Program Studi Teknologi Hasil Pertanian, 2025)
This study examines the effect of the ratio of gembili tuber flour and mocaf flour, as well as the addition of eggshell flour, on the chemical and organoleptic properties of gembili tuber cookies produced. In addition, it aims to determine the treatment that produces the best gembili tuber cookies that are preferred for consumption. The experiment used a Completely Randomized Block Design (CRBD) with two factors. The first factor was the variation in the ratio of gembili flour to mocaf flour (100:0, 80:20, 60:40) w/w, while the second factor was the concentration of eggshell flour (3%, 6%, 9%) w/w.The results showed that the ratio of gembili flour to mocaf flour affected ash content, moisture content, fat content, protein content, calcium content, carbohydrate content, color preference, and texture preference of gembili cookies, but did not affect taste preference or aroma preference.The percentage of eggshell flour affected moisture content, ash content, protein content, fat content, carbohydrate content, calcium content, aroma preference, taste preference, and texture preference of gembili cookies, but did not affect color preference.The formulation capable of producing the best cookies was A2B3 (ratio of gembili tuber flour to mocaf flour = 80:20% and addition of 9% eggshell flour). These cookies had an average preference score of 5.73 (somewhat like), moisture content of 2.21%, ash content of 5%, protein content of 3.08%, fat content of 21.06%, carbohydrate content of 68.66%, and calcium content of 3.81 mg/100 g.